Factors affecting blood lactate accumulation and clearance in elite competitive swimmers during competition - Wells, G. D.; Falenchuk, O.; Gannon, G.; Vescovi, J. D. (Biomechanics and Medicine in Swimming XI, 2010)
Blood lactate accumulation [BLa] occurs during competitive swimming events and may be influenced by demographic features as well as the characteristics of the swim race. Active recovery after high intensity exercise enhances blood lactate removal, which is beneficial for sports like swimming where multiple events are commonly performed on a single day. The objectives of this field-based observational study were 1) to examine how sex, age, race distance, and swim stroke influenced [BLa] after competitive swimming events and 2) to develop a practical model based on recovery swim distance to help optimize blood lactate disappearance. One hundred swimmers (n=50 males and females) competing in the Canadian National Swim Championships participated in this study. Post-race [BLa] was determined after completing the finals race. Blood lactate concentration was also assessed repeatedly during the warm-down. Generalized estimating equations were used to evaluate the relationship between post-race [BLa] with age and sex of the swimmers as well as the swim stroke and race distance. To evaluate the influence of warm-down distance on blood lactate disappearance an exploratory model building approach was used. The highest postrace [BLa] were observed following 100 and 200 metre events, the lowest after 50 and 1500 metre races. A sex effect for post-race [BLa] was observed for freestyle events, but not for any other swim strokes. There was a negligible effect of age on post-race [BLa]. The following model was developed to estimate an expected change in [BLa] during warm-down: [BLa] change after warm-down = -3.374+1.162(male=0; female=1)+0.789*post-race [BLa]+0.003*warm-down distance. These findings indicate that elite male and female swimmers competing at an elite level (approximately 900 FINA points) display similar post-race [BLa] and that there is little effect of age on post-race [BLa] in competitive swimmers 14-29 years old. Additionally, 50 metre events, regardless of swim stroke, appear to place less emphasis on anaerobic glycolysis compared to 100-400 metre events. Finally, a convenient equation was developed that can help coaches individualize warm-down protocols.